IMPLEMENTATION OF RESTORATIVE JUSTICE IN THE SETTLEMENT OF TRAFFIC ACCIDENTS PERFORMED BY UNDERAGES (Study at the Police Traffic Unit – Cirebon City) - Sunardi, Sunardi; Parmono, Budi; Taufik, Taufik (Universitas Islam Malang, 2022)
Traffic accidents involving minors have increased from year to year due to the lack of orderly traffic, as for the formulation of the problem in this thesis, how to apply restorative justice to traffic accident cases committed by minors in the jurisdiction of the Polres - Cirebon City and to find out the problems and solutions.This study uses a sociological juridical research method with descriptive analysis specifications based on primary data and secondary data. Primary data was obtained by means of interviews and secondary data obtained by literature study and then analyzed qualitatively. Research problems are analyzed with law enforcement theory, accountability theory and restorative justice theory.Based on the research results, the mechanism for solving traffic accident cases committed by minors with a restorative juctice approach at the Cirebon City Police Traffic Unit at the Cirebon City Police Traffic Accident Unit, namely when an accident occurs, the first thing to do is to process the crime scene. (TKP) for victims and perpetrators, both of them. After processing the TKP, the police make a TKP processing report, from the minutes the police get evidence from the accident case; The investigators carried out the investigation, after the investigation process, they were given time for the victims and perpetrators to argue, from this process Restorative Justice began to occur; If the victim and perpetrator are willing to reconcile and the perpetrator is willing to pay compensation, the parties make a statement of peace and agree not to proceed with the case in court;Another barrier to the use of restitution as a remedy for traffic accidents is:1) Traffic accidents caused by the death of the victim;2) The victim is unwilling to make peace3) It is difficult to find common ground for material compensation given between the perpetrators and the victims.Efforts made to overcome obstacles in the implementation of restorative justice in traffic accidents are conducting Enlightenment related to Traffic Law No. 22 of 2009 concerning Road Transport Traffic and Head of Police Regulation Number 15 of 2013 concerning Procedures for Settlement of Traffic Accidents, Help mediate both parties and carry out fast processing/handling of cases of minor traffic accidents which result in material losses with small/minor damage values but are still carried out in accordance with the provisions and regulations in force.Keywords: Traffic Accidents, Minors, Restorative justice.